STRATEGI PENGEMBANGAN KARIR GURU PAI - Aminah, Siti; Merliana, Setia Rini; Putra, Deko Rio (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze career development strategies for Islamic Religious Education (PAI) teachers in facing the challenges of globalization and technology. Today, teachers are no longer merely holders of professional titles; they must also be professional in their field. Professionalism plays a significant role in the success of the teaching and learning process, thereby improving the quality of education in Indonesia. Through career development strategies, teachers can adapt to changing times, particularly in the face of advances in educational technology and curriculum changes. The research method used in this paper is a library research approach, compiling various relevant literature, such as books and journals of national and international standards. The results indicate that career development for Islamic Religious Education (PAI) teachers can be achieved in the short, medium, and long term through various self-development activities such as training, seminars, certification, and scientific research.